2019
DOI: 10.1101/602334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Random forest-based modelling to detect biomarkers for prostate cancer progression

Abstract: 24The clinical course of prostate cancer (PCa) is highly variable, demanding an individualized 25 approach to therapy and robust prognostic markers for treatment decisions. We present a 26 random forest-based classification model to predict aggressive behaviour of PCa. DNA 27 methylation changes between PCa cases with good or poor prognosis (discovery cohort with 28 n=70) were used as input. The model was validated with data from two large independent 29

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Due to the high recurrence rate and poor outcome of advanced PCa, and several researchers built the prognosis predict features to judge the outcome and provide more effeteness treatment for PCa patients. Toth et al [36] generated a DNA methylation-based prognosis signature with the AUC of 0.95 in the training cohort, however, the AUC value in two external validation cohorts are only 0.771 and 0.687. Shao et al [37] produced a seven long noncoding RNAs signature to predict the RFS of PCa, with the AUC value of 0.68 and C-index value of 0.63, whereas this study lacks external validation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high recurrence rate and poor outcome of advanced PCa, and several researchers built the prognosis predict features to judge the outcome and provide more effeteness treatment for PCa patients. Toth et al [36] generated a DNA methylation-based prognosis signature with the AUC of 0.95 in the training cohort, however, the AUC value in two external validation cohorts are only 0.771 and 0.687. Shao et al [37] produced a seven long noncoding RNAs signature to predict the RFS of PCa, with the AUC value of 0.68 and C-index value of 0.63, whereas this study lacks external validation.…”
Section: Discussionmentioning
confidence: 99%
“…Random forests have been used in various aspects of prostate cancer research. [11][12][13][14][15] The current software represents the response to one of the 8 diseases considered in the Dr. Answer AI project. 9 The intention is to use the Dr. Answer AI software in hospitals from 2020, upon obtaining a software license from the Ministry of Food and Drug Safety.…”
Section: Discussionmentioning
confidence: 99%
“…RF approaches have been used in a variety of healthcare fields, including PCa research. [11][12][13][14][15] There existed a class imbalance problem in this study. The problem of data imbalance can be solved by 1) oversampling, 2) undersampling, and 3) combining oversampling and undersampling.…”
Section: Random Forest For Bcr Prediction Modelmentioning
confidence: 99%
“…Many studies recently reported that ZIC2 might regulate the development of various tumors, including prostate cancer (23,(34)(35)(36), lung adenocarcinoma (17), breast cancer, clear cell renal cell carcinoma (15,37,38), colorectal cancer (14, 39-41), hepatocellular carcinoma (13,(42)(43)(44), and cervical cancer (10,45). All these tumors, except breast cancer, were upregulated.…”
Section: Discussionmentioning
confidence: 99%